PENGARUH SEKTOR PERTANIAN DAN SEKTOR PERDAGANGAN, HOTEL DAN RESTORAN TERHADAP PRODUK DOMESTIK REGIONAL BRUTO (PDRB) KOTA DENPASAR - I Gusti Gde Oka Pradnyana (Forum Manajemen, 2012)
The success of a countryâ€™s development is inseparable from economicdevelopment activities in it. The ï¬ nal objective of the national development is tocreate social justice for all Indonesian people. Economic development is a plannedeffort and done in continuous basis to manage all existing resources to improvethe welfare of the community. Indonesia consists of many islands, Provincial andRegency / City, where the province of Bali and Denpasar City as one of them, then itseconomic development is the elaboration of the national development. The economicdevelopment of Bali province as well as Denpasar city actually driven by severalsectors, including agriculture and trade sectors, hotels and restaurants and a fewmore other sectors. The economy can be said to have a solid foundation if thosesectors has balanced contribution against its gross domestic product.This study istrying to see the inï¬‚ uence of agricultural and trade sector, hotels and restaurantsto the Gross Regional Domestic Product (GDP) of Denpasar. And the goal is todetermine the effect of those sectors to GRDP of Denpasar and which one of themare more dominant and how development of GDP in 2014. From the analysis ofthis study it can be concluded that the agricultural and trade sectors, hotels andrestaurants have a positive effect on GDP of Denpasar. It means that if those sectorsare increasing, the Denpasar GDP will increase, as evidenced by the slope coefï¬ cientof 4.836 obtained in the agricultural sector means that if the agricultural sector rose1%, the GDP rose 4.836%, while the sectors of trade, hotels and restaurants slopesector 1.971 means that if the trade, hotels and restaurants rose 1%, the GDP rose1.971%. Trade, hotels and restaurants have dominant inï¬‚ uence on the GDP about73.20%, while the GDP of Denpasar continues to rise each year becoming 16150.96billion in 2014.